Reconfiguring Media Space: Supporting Collaborative Work - Heath, Christian; Luff, Paul; Sellen, Abigail (Finn, K. Sellen, A. J. and Wilbur, S. B. (eds.), Video-Mediated Communication. Lawrence Erlbaum, 1997)
Advances in telecommunications will undoubtedly have a profound impact on organisational life and collaborative work over the next decade. Their ability to enhance and transform distributed activities, as well as enriching how people work when with each other, has been well documented and we wait with some impatience to witness the extraordinary contribution of such technologies to our ordinary lives. Despite the optimism that greet successive innovations in telecommunications, it is not at all clear whether current developments provide satisfactory support for even the most simple or apparently straightforward collaborative activities. Indeed, the debates which have arisen concerning the actual contribution of experimental systems when deployed in organisations such as research laboratories, reveal perhaps not only the potential shortcomings of the technology, but our lack of understanding of the ways in which it might contribute to interpersonal communication and collaborative work. Even the very basic question as to the advantage of audio-visual communication over basic telephony remains subject to debate and curiosity. In fact, we have been reliably informed that in a large scale study of the use of video telephones by domestic users in a city in South Western France, many subscribers preferred to look at themselves whilst on the phone rather than the person with whom they were talking. As yet therefore, we have relatively little understanding of the characteristics of videomediated communication or the contribution that audio-visual technologies including telecommunications might provide for collaborative work. In this brief chapter we wish to discuss the contribution and design of “media spaces”: computer-controlled networks of audio and video equipment intended to support collaboration among physically distributed colleagues. In particular, by exploring the actual use of media space technology and comparing the support it provides to the resources that people ordinarily rely upon when working together in more conventional environments, we wish to consider the requirements for developing more satisfactory technological environments for collaborative work. These requirements form the basis to a number of experiments in which we develop and evaluate prototype support for working together at a distance.